#
(t + 2)(t - 3) = t+2

solve this with step by step explanation

as quick as lighting do it

## Answers

Answered by

1

**Answer:**

t=3

**Step-by-step explanation:**

Cancel (t+2) from both sides and carry -3 to the RHS.

[Condition: if t is not equal to -2.]

Answered by

1

**Step-by-step explanation:**

(t+2)(t-3) = t+2

t(t-3)+2(t-3) = t+2

t²-3t+2t-6 = t+2

t²-t-6 = t+2

t²-t-t = 6+2

t²-2t = 8

t²-t = 8/2 = 4

t² = 4+t

t

Similar questions

Computer Science,
4 days ago

Science,
4 days ago

Math,
9 days ago

Math,
7 months ago

Social Sciences,
7 months ago

Science,
7 months ago